ROMAN CATHOLICS AND MUSLIMS IN GREECE: INTERRELIGIOUS AND INTERCULTURAL DIALOGUE IN A BALKAN COUNTRY (Религиски дијалог и соработка, 2025)
This paper is intended to analyse Islamic presence in Modern Greece especially under theperspective of interreligious dialogue between Muslim refugees and Christian majority of Greekpopulation. In this context, many initiatives held by Roman Catholics in Greece, especially Jesuits,Franciscans, local Caritas, Sisters of Mother Theresa, are devoted to Muslim refugees and peopleof different migratory background. Humanitarian activity promoted by Roman Catholics favoursan interactive process with immigrants but also a fight for justice with the result of establishingan interfaith dialogue with Greek Orthodox Christians. The meeting with refugees is aimed notonly to give them the possibility of making an income, but also to restore the dignity of migrantpeople. So, for example, the Jesuit Refugee Center (JRS) and the Jesuit Welcome Center (JWC) aremeant to answer the urgent needs of people from Central Asia (Pakistan, Afghanistan), Northernand Sahel Africa (Morocco, Egypt, Somalia, Nigeria) and other countries with Muslim majority. Onthe other hand, these initiatives favour a regular daily routine through work and/or learning. Thisgoal inspired the “Pedro Arrupe Center”, a social justice and educational project, aimed to helpyoung refugees or children of families with migratory background to better pursue their schoolintegration process.